The complex - Mahajan, Karan (Viking, 2026)
In a sprawling apartment complex in Delhi built by a powerful political patriarch, the members of the Chopra family struggle to build their own futures while living under the weight of his legacy. As India enters a time of political change, the family's ambitions, rivalries, and loyalties begin to collide. Sachin Chopra and his wife, Gita, attempt to start a new life in the United States, hoping to escape the pressures of the family compound. But the pull of home remains strong, especially as Sachin's uncle Laxman rises in a growing nationalist political movement and long-buried secrets begin to surface. As personal betrayals and political upheaval threaten the family's fragile unity, the Chopras must confront the true cost of power, ambition, and loyalty.